Caracterização de Campylobacter spp. isoladas em carcaças de frango - Feistel, Janaina Costa (2013)
Poultry products are recognized as sources of contamination by several pathogens. In the last decades the genus Campylobacter, particularly thermophilic species, stands out in developed countries, where it is considered the primary agent responsible for Foodborne Illnesses (DVA's). Due to the importance of this pathogen in public health and economics, researches are conducted in order to identify and characterize the isolated, as well as develop and improve techniques for the identification of the genus Campylobacter spp. with attention focused mainly to important thermophilic species related to food, allowing the determination of the prevalence of this pathogen in main placement sources, such as chicken. The objective of this study was to verify the occurrence of Campylobacter spp. and identify isolated thermophilic species from chicken carcasses in slaughterhouses in the state of Goiás submitted to the Federal Inspection Service which had proper authorization to internal and external trade. A total of 200 samples have been evaluated using the immunoenzymatic screening assay, with subsequent bacterial samples isolation and identification through biotyping. In this study it was observed that the employed methods allowed the isolation of Campylobacter spp. in 24% (48/200) of the assessed samples. Among these samples, 21 (10.5%) were demonstrably positive for genre, having as basis the set of analytical screening method, sequential bacterial isolation for positive samples and evidence of enzymatic and biochemical assimilation and antimicrobial profile. C.coli was the most frequently isolated species (58.6%), followed by C.jejuni ssp. jejuni (17.2%), C.lari (13.8%) and Campylobacter jejuni ssp. doylei (3.4%). By using a screening method, conventional isolation system and numerical biotyping it was immediately revealed the characterization of the isolated Campylobacter. It was observed that some suggestive isolated, due to its positivity in the screening test, growth on selective sources, incubation temperature, motility and morphology, characteristics of the genus assessed, have not been identified by numerical system and thus were considered negative. From the results, it can be concluded that the association of screening method to conventional isolation and biotyping numerical profile allowed a greater understanding of the isolated. It can also be concluded that Campylobacter spp. is present in chicken meat for human consumption and three thermophilic species and two subspecies have been identified. The pathogen presence attests public health risk.